Synchronizing the Utilization of the Population and Civil Registration Service Database for Bolaang Mongondow Utara Regency - Rahmawati Rahman; Lisda Van Gobel; Sofyan Alhadar (PT FORMOSA CENDEKIA GLOBAL, 2022)
The database of synchronization has not yet started because there are obstacles faced by government of the North Bolaang Mongondow Regency , causing the population data base to contain the data errors such as differences in population data. The data correction / or the latest data synchronization is needed to occur. This Research used the Types of Qualitative Research. The aim is to find out and analyze the synchronization of the use of population databases and civil records in North Bolaang Mongondow Regency. The results of this study indicate that the infrastructure of the Population and Civil Registry Office is still lacking in infrastructure, the socialization has been running but not optimal, the coordination that has been carried out is not optimal. It is need to add infrastructure, need to improve socialization and coordination so that services can be optimized.